Hyperglycemia in Patients of Acute Ischemic Stroke Presenting to Mardan Medical Complex, Mardan - Riaz, Kiran; Abbas, Muhammad; Noman, Muhammad; Kour, Komal; Khan, Waleed Ahmed; Rahman, Fazlu (Biological and Clinical Sciences Research Journal, 2025)
Hyperglycemia is a frequent metabolic disturbance in patients with acute ischemic stroke and is associated with poor neurological outcomes. Early identification and management of elevated blood glucose levels may improve clinical outcomes, yet its prevalence remains underreported in many regions of Pakistan. Objective: To determine the frequency of hyperglycemia in patients of acute ischemic stroke presenting to Mardan medical complex. Methodology: We carried out a cross-sectional study which was conducted at the Department of Medicine, Mardan Medical Complex from 19-10-2022 to 19-04-2023. Two hundred and twenty four patients having age 25–70 years diagnosed with acute ischemic stroke via radiological assessment were enrolled. We determined the frequency of hyperglycemia in these patients. Hyperglycemia was defined as capillary blood glucose (CBG) >140 mg/dL. Results: Mean age was 52.48±13.08 years. There were 125 (55.8%) male and 99 (44.2%) female patients. Hyperglycemia was present in 56.1% patients. Stratified analysis revealed notable associations of hyperglycemia with hypertension (P = 0.001) and BMI (P = 0.001). Conclusion: Frequency of hyperglycemia in patients of acute ischemic stroke in our study was 47.3%.